Medical Imaging 2020: Biomedical Applications in Molecular, Structural, and Functional Imaging 2020
DOI: 10.1117/12.2549406
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal muscle segmentation from CT using a convolutional neural network

Abstract: CT is widely used for diagnosis and treatment of a variety of diseases, including characterization of muscle loss. In many cases, changes in muscle mass, particularly abdominal muscle, indicate how well a patient is responding to treatment. Therefore, physicians use CT to monitor changes in muscle mass throughout the patient's course of treatment. In order to measure the muscle, radiologists must segment and review each CT slice manually, which is a time-consuming task. In this work, we present a fully convolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Recently, deep learning-based body composition segmentation at CT images was validated 29 31 and this technique could provide robust segmentation from noise 32 . In addition, deep learning also enables researchers to perform time-consuming process more easily 33 . We believe that utilization of deep learning-based technique can bring another breakthrough to body composition measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, deep learning-based body composition segmentation at CT images was validated 29 31 and this technique could provide robust segmentation from noise 32 . In addition, deep learning also enables researchers to perform time-consuming process more easily 33 . We believe that utilization of deep learning-based technique can bring another breakthrough to body composition measurements.…”
Section: Discussionmentioning
confidence: 99%
“…both used a VGG‐16 27 pre‐trained on ImageNet, a large‐scale natural image data set comprising over 14 million images belonging to 1000 categories, 28 to initialize the encoder in an FCN or U‐Net architecture, respectively. Although the authors train their models on much smaller data sets (250 and 160 axial CT slices, respectively) compared to those discussed previously, 18,20,21 we believe that further research surrounding optimization of the transfer learning procedure will allow much smaller training set sizes and in consequence, more adaptable models.…”
Section: Introductionmentioning
confidence: 97%
“…12 Several studies have shown promising results using deep learning-based methods for quantification of abdominal SM or adipose tissues. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] As CNNs require large amounts of data, it is common to use multiple available data sets for training purposes. However, no software is trained and tested on CT slices from different anatomical levels acquired from CRC patients.…”
Section: Introductionmentioning
confidence: 99%